Pengaruh Trustworthy dan Physical Attractive Influencer tehadap Niat Beli Produk Kuliner di JABODETABEK dengan Mediasi Citra Merek - Panesto, Rendy; Widjaja, Bernard T.; Wahyoedi, Soegeng (Universitas Bunda Mulia, 2024)
In this fast-paced information and communication technology era, social media influencers have established themselves as reliable and potential endorsers, generating widespread attention and being considered among the most effective and cost-efficient marketing strategies. This study aims to examine the effect of Influencer’s Trustworthiness and Physical Attractiveness on Purchase Intention of Culinary Products in JABODETABEK Mediated by Brand Image. The analytical method used in this study was Structural Equation Modeling (SEM) implemented through SmartPLS program. The sample in this study consists of Indonesian citizens residing in Jakarta, Bogor, Depok, Tangerang, and Bekasi areas who have watched food vlog content at least once in the past six months. Hypotheses were tested using quantitative methods, based on 92 samples collected via electronic questionnaires. The results of the study indicate that influencer’s trustworthiness and physical attractiveness do not have a direct influence on purchase intention. Conversely, influencer’s trustworthiness and physical attractiveness have a positive and significant impact on brand image. Furthermore, brand image positively and significantly affects purchase intention. Brand image also serves as a mediator in the relationship between trustworthiness and purchase intention, while it does not mediate the effect of physical attractiveness on purchase intention.